2012
DOI: 10.5334/jeps.at
|View full text |Cite
|
Sign up to set email alerts
|

The brain activity of pain relief during hypnosis and placebo treatment

Abstract: Placebo treatment and hypnosis are both examples of top-down regulation and are used to treat pain. However, it is unclear whether hypnosis produces anything more than a placebo effect when measuring brain activity changes. This literature review examines research articles published from 1997 onwards regarding the neurophysiology of pain relief during hypnosis or placebo treatments using functional brain imaging (fMRI or PET). The focus was on acute produced nociceptive pain. There seems to be both similaritie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…Historically, hypnosis has been a controversial topic, but advances in brain imaging techniques like functional MRI have shown it to involve neural activity patterns that distinguish it from simple suggestibility (Wagstaff, 2014), relaxation (Williams & Gruzelier, 2001), role-playing (Mende, 2009), or placebo (Kirjanen, 2012). Hypnosis is associated with lower global functional connectivity and reduced activity in anterior parts of the default-mode network (linked to processes such as task-independent thinking, episodic memory, semantic processing, and self-awareness; Deeley et al, 2012) and increased activity in prefrontal attentional systems (Oakley & Halligan, 2013).…”
Section: A Different View—hypnosismentioning
confidence: 99%
“…Historically, hypnosis has been a controversial topic, but advances in brain imaging techniques like functional MRI have shown it to involve neural activity patterns that distinguish it from simple suggestibility (Wagstaff, 2014), relaxation (Williams & Gruzelier, 2001), role-playing (Mende, 2009), or placebo (Kirjanen, 2012). Hypnosis is associated with lower global functional connectivity and reduced activity in anterior parts of the default-mode network (linked to processes such as task-independent thinking, episodic memory, semantic processing, and self-awareness; Deeley et al, 2012) and increased activity in prefrontal attentional systems (Oakley & Halligan, 2013).…”
Section: A Different View—hypnosismentioning
confidence: 99%
“…In addition, in a late processing stage common to both waking placebo and hypnotic placebo analgesia was the enhanced activity in the ACC. Research has shown that these cortical regions are part of a pain responsive network (i.e., somatosensory cortex, ACC, insula, perigenual cortex, pre-supplementary motor cortex, thalamus, and prefrontal cortex) [ 141 , 150 152 ] whose activity is modulated by the ongoing pain experience associated with hypnotic analgesia [ 20 , 32 , 33 , 58 , 153 , 154 ]. Thus, we think that regional differences in electro cortical activity, found between hypnotizability groups, reflect the higher pain/distress reduction reported by HH participants.…”
Section: Discussionmentioning
confidence: 99%
“…We have known, for a long time, that hypnotic analgesia is not a variant on placebo analgesia since highly hypnotizable individuals report feeling less pain during hypnosis than during placebo condition [ 19 ], suggesting that the effects of placebo and hypnosis analgesia are at least in part separate processes. A recent literature review on brain activity changes to placebo and hypnotic analgesia has highlighted similarities and differences between these two treatments [ 20 ]. First, these treatments produce similar changes in the activity of a number of brain regions labeled as pain network (i.e., somatosensory cortex, ACC, insula, thalamus, and prefrontal cortex).…”
Section: Introductionmentioning
confidence: 99%